Development and Evaluation of an Immunochromatographic Strip and a Magnetic Chemiluminescence Immunoassay for Detection of Porcine Circovirus Type 2 Antigen - Sirui Tao; Yu Duan; Yinhe Zha; Xiaxia Tong; Yulong He; Huapeng Feng; Jianhong Shu (Veterinary Sciences)
Porcine circovirus type 2 (PCV2) is the main and primary causative agent of Postweaning Multisystemic Wasting Syndrome (PMWS). To date, immunoperoxidase monolayer assay (IPMA), indirect immunofluorescent assay (IFA), and enzyme linked immunosorbent assay (ELISA) are the most commonly diagnostic methods for detecting PCV2 antigens. However, these methods require specialized equipment and technical expertise and are suitable for laboratory use only. This study aims to develop an immunochromatographic strip and a magnetic chemiluminescence immunoassay for the detection of PCV2 antigens. The recombinant protein was constructed using a prokaryotic expression system, and the polyclonal antibody was obtained by animal experiments. Polystyrene microspheres are used as solid phase carriers to covalently bind to the amino groups of proteins to form immunoprobes. Monodisperse beads are covalently bound to antigens or antibodies as solid phases to bind antibodies or antigens in the liquid phase in a superior manner, thereby capturing and separating antigens and antibodies in the liquid phase. The immunochromatographic strip is qualitative detection method, this method can detect PCV2a strain, PCV2b strain, and PCV2d strain. The immunochromatographic strip had minimum detection limits of 102.89TCID50/0.1 mL, 103.19TCID50/0.1 mL, and 103.49TCID50/0.1 mL for PCV2a/LG, PCV2b/SH, and PCV2d/JH. The results of testing PEDV (CV777 strain), PRV (HB2000 strain), CSFV (WH-09 strain), PRRS (JXA1-R strain), PPV (WH-1 strain), and ASFV (SD strain) were negative. The agreement between the immunochromatographic strip and the ELISA kit was 93.33% (140/150) and the Kappa was 0.866 (Kappa > 0.81). On the premise of ensuring sensitivity, the most important feature of the immunochromatographic strip is that this method can save time when testing; results can be obtained within 5 to 10 min. Magnetic chemiluminescence immunoassay is quantitative detection method; this method can detect PCV2 Cap proteins in swine serum, the linear range of this method was 0.25 ng/mL to 32 ng/mL and R2 of the standard curve was 0.9993. The limit of detection (LOD) is 0.051 ng/mL and the limit of quantitation (LOQ) is 0.068 ng/mL. The agreement between the magnetic chemiluminescence immunoassay and the ELISA kit (test PCV2 Cap proteins) was 97.14% (68/70). This method took less than 30 min to achieve results, which is less than the ELISA kit. The results of this study show that immunochromatographic strip and magnetic chemiluminescence immunoassay for PCV2 antigens had great sensitivity and specificity, which lays the foundation for PCV2 clinical detection.